Liturgias vigiadas, católicos divididos: como a crise de pertencimento esvazia os ritos = Observed liturgies, divided catholics: how the crisis of belonging empties the rites = Liturgias supervisadas, católicos divididos: cómo la crisis de pertenencia vacía los ritos - Leite, Pedro (Teocomunicação, 2024)
This article aims to reflect on the contemporary phenomenon of emptying community bonds. The starting point is the identification of subjectivism as responsible for the crisis of belonging that generates a process of individual atomization and enclosure. The person at this level of crisis can find other atomized subjects who associate forming new grouping with the same characteristics: uniformization of ideas and election of common enemies. This new associative configuration, hostage to a charismatic leader, finds in social media the necessary reinforcement for the proliferation of its doctrines and hermeneutics without the own refutation of interpersonal relationships. Such atomized individuals become intransigent watchmen, provoking a gradual and violent division among Catholics. From this analytical construction, we will observe the rites as an aspect of the Catholic liturgy that is affected by such a crisis, since the celebratory structure does not know the isolated self, but is always thought on the perspective of us from the Church. Finally, some outputs are presented with the goal of intersubjective, dialogical and synodal relations.